2006
DOI: 10.1677/joe.1.06794
|View full text |Cite
|
Sign up to set email alerts
|

Cell specificity of the cytoplasmic Ca2+ response to tolbutamide is impaired in β-cells from hyperglycemic mice

Abstract: We recently reported that the timing and magnitude of the nutrient-induced Ca 2C response are specific and reproducible for each isolated b-cell. We have now used tolbutamide and arginine to test if the cell specificity exists also for the response to non-nutrient stimulation of b-cells and if so, whether it is disturbed in b-cells from hyperglycemic ob/ob and db/db mice. Zn 2C outflow measurements were used to study the correlation between Ca 2C response and insulin secretion in individual b-cells. Tolbutamid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…When Lepr flox/flox RIP-Cre islets were stimulated with tolbutamide a significant reduction in the Ca 2+ influx was found compared to control Lepr flox/flox islets. Similar observations have been reported from leptin receptor deficient db/db β-cells, which show a diminished response to tolbutamide [39]. In addition, defective electrical activity characterized by altered [Ca 2+ ] i -activated K + permeability or decreased L-type Ca 2+ currents has been described in islets from different diabetic models [40], [41].…”
Section: Discussionsupporting
confidence: 81%
“…When Lepr flox/flox RIP-Cre islets were stimulated with tolbutamide a significant reduction in the Ca 2+ influx was found compared to control Lepr flox/flox islets. Similar observations have been reported from leptin receptor deficient db/db β-cells, which show a diminished response to tolbutamide [39]. In addition, defective electrical activity characterized by altered [Ca 2+ ] i -activated K + permeability or decreased L-type Ca 2+ currents has been described in islets from different diabetic models [40], [41].…”
Section: Discussionsupporting
confidence: 81%
“…OM ß-cells have an increased Na/K-ATPase activity [50] and may be more sensitive to voltage-dependent events [51], but an impaired function of voltage-dependent Ca 2+ channels [52] and a disturbed pattern of cytoplasmic calcium changes after glucose stimulation has also been reported [53]. They also do not show the same type of cell-specific Ca 2+ responses that are found in lean mouse islets [54]. There is an excessive firing of cytoplasmic Ca 2+ transients when OM ß-cells are stimulated with glucagon [55].…”
Section: Pancreatic Isletsmentioning
confidence: 99%
“…To identify the roles of the putative GPR55 ligands O‐1602, LPI and CBD in β‐cells, and to examine the requirement of GPR55 for their functional effects, [Ca 2+ ] i was measured by single cell microfluorimetry in islets isolated from WT and GPR55 −/− mice. Previous studies have identified β‐cell responses in dispersed islet populations through elevated [Ca 2+ ] i levels in response to stimulatory concentrations of glucose and to the K ATP channel blocker tolbutamide, so in our experiments dispersed islet cells were classified as β‐cells if they responded to 20 mM glucose and to 100 μM tolbutamide. Figure A shows that 10 μM O‐1602 caused a rapid and reversible increase in [Ca 2+ ] i in WT islet β‐cells at 2 mM glucose, and these cells then responded to 20 mM glucose with a similar amplitude of calcium increase (peak response, 340 : 380 ratio: 0.821 vs. 0.815).…”
Section: Resultsmentioning
confidence: 99%